Where is the joined-up thinking?. (2nd September 2021) - Allingham, Sue
Abstract : It is vital to reflect on our practice and provision and adapt appropriately, but this also requires the government to do the same. Dr Sue Allingham questions why there isn't joined-up thinking about what is important across the sector, including how early childhood education should work.